Hospital Pharmacy Preparedness and Pharmacist Role During Disaster in Saudi Arabia - Aljabri A; Bakhsh H; Baageel A; Al-Nimari S; Alshehri S; Bakadam B; Almasrahi S; Kutbi H (Dove Medical Press, 2021)
Ahmed Aljabri,1,2 Hussain Bakhsh,1 Abeer Baageel,3 Sara Al-Nimari,3 Samah Alshehri,1,4 Bashayer Bakadam,3 Shaima Almasrahi,3 Hussam Kutbi1 1Department of Pharmacy Practice, Faculty of Pharmacy, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 2Department of Pharmacy Practice, Faculty of Pharmacy, University of Tabuk, Tabuk, 71491, Saudi Arabia; 3Faculty of Pharmacy, King Abdulaziz University, Jeddah, 21589, Saudi Arabia; 4College of Pharmacy, University of Arizona, Tucson, AZ, 85721, USACorrespondence: Ahmed AljabriDepartment of Pharmacy Practice, Faculty of Pharmacy, King Abdulaziz University, Jeddah, 21589, Saudi ArabiaTel +966126400000/21146Fax +966126951696Email amaljabri@kau.edu.saBackground: In case of emergencies, the number and severity of mass casualties may exceed medical services resources. Saudi Arabia is prone to different disasters, and all medical resources should be ready and prepared to serve during disasters. Pharmacists are essential during disasters; however, their roles have not been well studied during disasters in Saudi Arabia.Methods: An observational cross-sectional study targeted tertiary hospitals in Jeddah. An electronic survey, consisting of 34 questions, was developed and distributed to pharmacy directors or their representatives to investigate the hospital pharmacies' preparedness and pharmacist roles during disasters in the city of Jeddah.Results: Six hospitals participated in the survey, with a 100% response rate. All respondents confirmed the presence of disaster plans involving pharmacy departments. Hospital committee consensuses determined which medication to stock in five hospitals (83.3%). All six respondents (100%) agreed that the following medication supplies were adequate in the event of disasters: analgesics, rapid sequence intubation medications (ie, sedatives and paralytics), respiratory medications, antimicrobials, and maintenance intravenous (IV) fluids. There was disagreement on the adequacy of wound infection prophylaxis, vasopressors/inotropes, antiemetic medications, ophthalmic medications, and antidotes for chemical weapons. There were discrepancies on pharmacist roles during disaster, but hospitals agreed on the following roles: maintain effective distribution and control, collaborate on medication management, and develop and maintain first-aid skills.Conclusion: All included facilities have emergency preparedness plans for the hospitals and the pharmacy departments. However, the type and quantities of stocked medications, as well as pharmacist roles, are not well recognized. The results highlight the need for national guidance to enhance and support the preparedness of healthcare facilities.Keywords: hospital pharmacy, mass casualty, disaster, pharmacist roles, emergency preparedness